2013
DOI: 10.1002/jsfa.6000
|View full text |Cite
|
Sign up to set email alerts
|

Soil threshold values of total and available cadmium for vegetable growing based on field data in Guangdong province, South China

Abstract: Cadmium-contaminated risk for vegetable production in Guangdong province might have been over-estimated according to the Chinese Environmental Quality Standard for Soil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…The heavy metal uptake of vegetables in the artificial addition experiment with heavy metal salt solutions is usually expected to be higher than that in the field situation (Alexander et al 2006;Yang et al 2009;Zhang et al 2010). Based on the field samples of three leafy vegetable species, Sun et al (2013) determined the soil threshold values of total Cd and available Cd (2.42 and 1.08 mg kg -1 , respectively) for leafy vegetables in Guangdong Province. A case study on safe limit of the soil As from West Bengal also suggested that the permissible limit of Olsen-extractable As and total As in soil for rice cultivation were varied according to the soil pH and organic carbon contents in different regions (Golui et al 2017).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The heavy metal uptake of vegetables in the artificial addition experiment with heavy metal salt solutions is usually expected to be higher than that in the field situation (Alexander et al 2006;Yang et al 2009;Zhang et al 2010). Based on the field samples of three leafy vegetable species, Sun et al (2013) determined the soil threshold values of total Cd and available Cd (2.42 and 1.08 mg kg -1 , respectively) for leafy vegetables in Guangdong Province. A case study on safe limit of the soil As from West Bengal also suggested that the permissible limit of Olsen-extractable As and total As in soil for rice cultivation were varied according to the soil pH and organic carbon contents in different regions (Golui et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The geographic coordinates of Guangdong Province is 20°10´-25°31´N and 109°41´-117°17´E which represents an area of 1.78×10 5 km 2 in South China. The whole area is characterized by a sub-tropical monsoon climate with mean annual precipitation of 1 336 mm and mean annual air temperature of 21.1°C (Sun et al 2013). The typical soil profile is Al-enriched weathering profile developed on a variety of rocks, such as granite, sand shale, limestone and basalt, with granite as the most extensive parent rock (occupying more than 40% of the Guangdong area) .…”
Section: Study Sitesmentioning
confidence: 99%
See 3 more Smart Citations